Viabilidade do aproveitamento da biomassa energética na colheita de povoamento de Pinus em primeiro desbaste - Pelissari, Carla Krulikowski Rodrigues (2017)
The aim of this study was to carry out an operational evaluation, quantify and characterize the energy biomass and determine the energy and carbon stocks in Pinus taeda L. stands of different ages and under thinning regime. Specifically, the objective was to quantify the energy biomass produced in the stands by means of the wood harvesting operations; to verify the influence of variables in cutting and extraction operations; and quantify the biomass energy potential and carbon dioxide emissions at the different ages of the stands. The study was carried out at the Araupel company, located in the municipality of Quedas do Iguaçu, Paraná State, in which the data were obtained in stands at 7, 8, 9, and 10 years old in the mixed thinning method with removal of 50% of all trees and carried out in a systematic mode in the fifth line of the stand and in the adjacent lines of selective mode. Initially, volume and above-ground biomass were quantified by destructive method, in which the trees were segmented in saw wood, firewood, tip, leaves, bark, and branches. Subsequently, a technical and cost evaluation of the harvester and forwarder machines was carried out for determining operational efficiency, energy efficiency, productivity, and operational and production costs. The variables that influenced in the execution of the operations were analysed by statistical modeling. The firewood, tips, leaves, barks, and branches were analysed for determining the energy potential of stands, by means of basic specific mass, higher and inferior heating value, chemical composition and determination of the fuel value index. The results showed that the best ages for applying thinnings that aim woody biomass were 9 and 10 years old, with a largest production of saw wood. When evaluating the harvesting of the wood in the thinning at these ages, it was verified that the average harvester productivity was 26.5 and 25.1 m³ per hour effective (he), with average production cost of R$ 4.74 m-3 and R$ 5.00 m-3 , while the forwarder was 37.0 and 37.6 m³ he-1 , with average production costs of R$ 4.89 m-3 and R$ 4.81 m-3 for the ages 9 and 10 years old, respectively. For estimating productivity and costs of the machines, it was verified significant influence of the individual volume on the productivity and production costs of the harvester, while the load volume influenced on the productivity and production costs of the forwarder. When evaluating the energy production from the energy biomass it was verified that the potential was similar in all evaluated ages. In relation to the energy characteristics of thin firewoods and residues, the ages 9 and 10 years old stood out in relation to the fuel value index, mainly in the components firewood, tips, and branches. In this way, it was verified that the usage of the residual biomass of the wood harvesting presents viability in the energy generation, being similar to the amount of energy and the potential of CO2 emission in the different ages of the stands.